Chemical diagnostics : from bench to bedside - Tang, Nelson L. S., editor; Poon, Terence, editor (Heidelberg : Springer, 2014)
Next Generation Sequencing: Chemistry, Technology and Applications, by P. Hui Application of Next Generation Sequencing to Molecular Diagnosis of Inherited Diseases, by W. Zhang, H. Cui, L.-J.C. Wong Clinical Applications of the Latest Molecular Diagnostics in Noninvasive Prenatal Diagnosis, by K.C.A. Chan The Role of Protein Structural Analysis in the Next Generation Sequencing Era, by W.W. Yue, D.S. Froese, P.E. Brennan Emerging Applications of Single-Cell Diagnostics, by M. Shirai, T. Taniguchi, H. Kambara Mass Spectrometry in High-Throughput Clinical Biomarker Assays: Multiple Reaction Monitoring, by C.E. Parker, D. Domanski, A.J. Percy, A.G. Chambers, A.G. Camenzind, D.S. Smith, C.H. Borchers Advances in MALDI Mass Spectrometry in Clinical Diagnostic Applications, by E.W.Y. Ng, M.Y.M. Wong, T.C.W. Poon Application of Mass Spectrometry in Newborn Screening: About Both Small Molecular Diseases and Lysosomal Storage Diseases, by W.-L. Hwu, Y.-H. Chien, N.-C. Lee, S.-F. Wang, S.-C. Chiang, L.-W. Hsu